2013
DOI: 10.1007/s11060-013-1186-3
|View full text |Cite
|
Sign up to set email alerts
|

A population-based study of low-grade gliomas and mutated isocitrate dehydrogenase 1 (IDH1)

Abstract: Low-grade gliomas (LGG) have a slow growth rate, but transformations into malignant gliomas with a rapid deterioration occur in many patients. The aim of this study was to evaluate clinical prognostic factors in a population-based cohort of patients with LGG. In addition we investigated the expression and prognostic value of the isocitrate dehydrogenase 1 (IDH1) R132H mutation. Seventy-four patients diagnosed between 2005 and 2009 in the Region of Southern Denmark were identified using the Danish Cancer Regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 48 publications
3
39
1
Order By: Relevance
“…This is in accordance with a study performed in our group [15], which showed that all patients do benefit from the Stupp regimen. The benefit is largest in patient younger than 60 years as compared to patients aged 60-70 years and 70+.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is in accordance with a study performed in our group [15], which showed that all patients do benefit from the Stupp regimen. The benefit is largest in patient younger than 60 years as compared to patients aged 60-70 years and 70+.…”
Section: Discussionsupporting
confidence: 93%
“…In this material, we did not have access to information regarding the proportion of cancers with a histological verification of the diagnosis, and it is difficult to interpret the results for the different histological subgroups of CNS tumors. However, based on a material of histologically verified malignant gliomas, we showed a similar trend in these patients [15]. To our knowledge studies regarding elderly patients and treatment have only been published regarding patients with malignant gliomas.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Response assessment is susceptible to considerable inter-observer variability and this may explain most of the difference in our observed response rates and why we were not able to predict 19 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) 18 11 (5- Figure 1. Survival of risk groups.…”
Section: Discussionmentioning
confidence: 94%
“…Median survival of GB patients treated with aggressive multimodal thera py, including total resection, combined radiation and chemotherapy, and adjuvant chemotherapy is about 12 months [9,18,24,25]. Glioblastoma is actually con sidered a heterogeneous and dynamic disease [13,17,21].…”
Section: Introductionmentioning
confidence: 99%